Legal Certainty of Follow the Money Approach on the Execution of Replacement Money for In Absentia Corruption - Shinfani Kartika Wardhani; Hervina Puspitosari (Faculty of Law, Universitas Lampung, 2026)
The implementation of additional criminal sanctions for asset recovery under Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 on the Eradication of Corruption Crimes faces significant challenges at the execution stage, particularly when convicts are listed as fugitives on the wanted list (DPO). Law enforcement conducted in absentia through a “follow the money” approach lacks an integrated regulatory framework, despite the asset recovery concept being adopted in Indonesia since the early 2000s. This study examines the legal certainty of the “follow the money” approach in the execution of asset recovery orders in in absentia corruption cases. Using a normative juridical method with statutory and conceptual approaches, the study finds that the current ius constitutum remains fragmented and is dominated by internal prosecutorial guidelines that are not systematically integrated across law enforcement agencies. This normative fragmentation creates a deficit of legal certainty in efforts to recover state financial losses. Therefore, regulatory synchronization is required to ensure effective legal certainty in accordance with the principles of the justice system.